Pandangan Hakim PA Pasuruan tentang Hukuman Pelaku Nikah Sirri dalam RUU Hukum Materiil PA Bidang Perkawinan - Khilyatus Sa’adah (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
This paper aims to determine the views of Judge PA Pasuruan about the punishment of Sirri marital offenders in the Marriage Law Draft Bill on Marriage, which will then be analyzed with the theory of mas} lah} ah mursalah. At the end of the paper, it was concluded that, first, the Judges of the Pasuruan Religious Court mostly agreed on the punishment for the perpetrators of marriages sirrî in article 143 of the Draft Law of the Religious Courts in the field of Marriage, because there were too many negative impacts caused by marriagesirrî, such as the recognition of civil rights. wife, is not considered a legitimate wife and is not entitled to gonogini assets in the event of separation. The basic consideration of the judge of the Pasuruan Religious Court agreed to the punishment for the perpetrators of marital sirrî, namely by using the concept of mas} lah} ah mursalah which is something that is good according to reason with consideration of realizing good or avoiding evil for humans, what according to reason is also in harmony and in line with the objectives syara 'in establishing the law. The punishment for the perpetrators of the marriage of sirrî is solely intended to seek the benefit of humans because of the more harm that arises from the marriage of Sirri. This is in accordance with the principles of jurisprudence: "Refusing the damage takes precedence over attracting benefit."